Monkeys - Schreiber, Anne. (Washington, D.C. : National Geographic, 2013)
Collects facts about monkeys, describing their physical characteristics, behaviors, and habitat.
Monkey business -- Monkeying around -- All in the family -- Monkey babies -- Tools of the trade -- Want a banana? -- 6 Marvelous monkeys -- Friends and family -- Monkeys in trouble -- Stump your parents.
2.7
K-3
K-3
Keywords: Monkeys -- Juvenile literature; Monkeys; Monkeys; Readers (Elementary)